Intensity modulated radiotherapy delivers competitive local control rate with limited acute toxicity in the adjuvant treatment of rectal cancer. (4th June 2018) - Lee, Cheng-Yen; Chang, Chih-Chia; Yang, Hsin-Yi; Chiang, Pin-Yi; Tsang, Yuk-Wah
Abstract : This study on IMRT as part of adjuvant treatment of rectal cancer has shown competitive local control rate. Concurrent chemotherapy may be associated with increased risk of hematotoxicity. Abstract: Background: Intensity-modulated radiotherapy (IMRT) has yet to show its capability in the adjuvant treatment of locally advanced rectal cancer. The purpose of this study is to evaluate the clinical efficacy and safety profile of IMRT in the adjuvant treatment of rectal cancer. Method: Consecutive patients with resected locally advanced rectal cancer who had IMRT as part of adjuvant treatment between 2008 and 2014 were identified. The medical records and dosimetric parameters of 72 patients were retrospectively examined. Results: The median follow-up time was 4.36 years (range 0.16–8.49 years). Overall survival rate and disease-free survival rate at 3 year was 79% (95% CI: 66.4–7.3%) and 70% (95% CI: 56.6–79.6%), respectively. Local control rate was 95%. The median bowel bag V45 was 282 ml (249–458 ml) and bone marrow V40 was 29%. Most acute toxicities were self-limited. Concurrent use of chemotherapy was associated with greater odds of ≥Grade 2 acute neutropenia (OR 25.44, P = 0.022). Conclusion: Integration of IMRT in the adjuvant treatment of rectal cancer is promising with competitive local control rate. Acute toxicities are mostly self-limited.